Artificial intelligence and government - Martinho-Truswell, E; Martin, S (Future Leaders, 2019)
Artificial intelligence offers a daunting challenge for government: a potent mix of high expectations, big budgets, a competitive international “AI arms race”, and elevated public fears. Some governments, such as China, France and Canada, are determined that their countries be leaders in AI; others have been slower to make public policy statements but may be watching to see where their country might best fit in a field that is moving quickly.